ADMINISTRATIVE CHANGE IN THE EU: A CROSS‐COUNTRY EMPIRICAL STUDY ON THE CONTEXTUAL DETERMINANTS OF NPM REFORM RHETORIC. (4th August 2016) - ESPOSITO, Giovanni; GAETA, Giuseppe Lucio; TRASCIANI, Giorgia
ABSTRACT: Framed within the paradigm of New Public Management (NPM), structural reforms in the EU aimed at modernizing the public administrations of Member States (MSs) have long since been a priority area of the EU's economic policy. Since the 1990s, these reforms have been sharply intensified across European countries with the declared purpose of enhancing economy, efficiency and effectiveness in their national public sectors' organizations. In line with the European Commission's recent research initiatives in search for novel quantitative data on NPM in the EU, this paper studies European parties' NPM reform rhetoric. More specifically, it investigates the MSs' institutional, economic and political context within which parties have declared their intention of reforming national administrative systems. Thus, it sheds light on the MSs' domestic factors that are associated with the diffusion of the NPM values across the political discourse of EU's national parties.